A student solves the following problem:
Problem:
2(x−3) + 3x = 19
Step 1: 2x − 6 + 3x = 19
Step2: (2x + 3x) −6 = 19
Step 3: 5x − 6 = 19
Step 4: 5x - 6 + 6 = 19 + 6
Step 5: 5x = 25
Step 6: x = 5
What property justifies going from step 3 to step 4?
Responses
Substitution Property
Substitution Property
Commutative Property of Addition
Commutative Property of Addition
Distributive Property
Distributive Property
Addition Property of Equality
Addition Property of Equality
Division Property of Equality
Division Property of Equality
Skip to navigation
1 answer
Addition Property of Equality